TRANSPORMASI ALQURAN DALAM NOVEL MELATI TUHAN KARYA IMAM WICAKSONO - Rahman Hidayat (MUMTAZ : Jurnal Pendidikan Agama Islam, 2024)
This research aims to identify the relationship between the Quran and the novel "Melati Tuhan" written by Imam Wicaksono. This study is qualitative, with data consisting of words, phrases, sentences, and discourse related to the Quran found in the novel "Melati Tuhan." Data analysis in this paper uses an intertextual approach. The findings of this research reveal several connections between the Quran and the novel "Melati Dewa," including: (1) The purpose of human creation as mentioned in QS. Az-Zariyat (51): 56, (2) Gratitude in all situations and conditions as described in QS. Ibrahim (14): 7. (3) Allah tests humans according to their abilities as stated in QS. Al-Baqarah (2): 286, (4) Nothing is impossible with Allah as noted in QS. Yasin (36): 82, (5) Every decree of Allah is the best for His servants as detailed in QS. Al-Baqarah (2): 216, and (6) Every good and evil deed receives a response as indicated in QS. Al-Zalzalah : 7-8.